Association Study of Tumor Necrosis Factor Receptor 1 (TNFR1) Gene Polymorphisms with Schizophrenia in the Polish Population - Suchanek-Raif, Renata; Kucia, Krzysztof; Kowalczyk, Małgorzata; Raif, Paweł; Paul-Samojedny, Monika; Fila-Daniłow, Anna; Kowalski, Jan (Mediators of Inflammation, 2017)
Schizophrenia is a devastating mental disorder with undetermined aetiology. Previous research has suggested that dysregulation of proinflammatory cytokines and their receptors plays a role in developing schizophrenia. We examined the association of the three single nucleotide polymorphisms (SNPs; rs4149576, rs4149577, and rs1860545) in the tumor necrosis factor receptor 1 (TNFR1) gene with the development and psychopathology of paranoid schizophrenia in the Polish Caucasian sample consisting of 388 patients and 657 control subjects. The psychopathology was assessed using a five-factor model of the Positive and Negative Syndrome Scale (PANSS). SNPs were genotyped using the TaqMan 5′-exonuclease allelic discrimination assay. The SNPs tested were not associated with a predisposition to paranoid schizophrenia in either the entire sample or after stratification according to gender. However, rs4149577 and rs1860545 SNPs were associated with the intensity of the PANSS excitement symptoms in men, which may contribute to the risk of violent behavior. Polymorphisms in the TNFR1 gene may have an impact on the symptomatology of schizophrenia in men.